2007
DOI: 10.1038/sj.onc.1210571
|View full text |Cite
|
Sign up to set email alerts
|

TrkC binds to the type II TGF-β receptor to suppress TGF-β signaling

Abstract: Growing evidence suggests that overexpression of TrkC, a member of the Trk family of neurotrophin receptors, could drive tumorigenesis, invasion and metastatic capability in cancer cells. However, relatively little is known about the mechanism of TrkC-mediated oncogenesis. The TrkC gene is a partner of the Tel-TrkC (ETV6-NTRK3) chimeric tyrosine kinase, a potent oncoprotein expressed in tumors derived from multiple cell lineages. Recently, we have shown that ETV6-NTRK3 suppresses transforming growth factor-b (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
1
23
3
Order By: Relevance
“…Along these lines, we also observed p130Cas expression to be up-regulated dramatically in the murine 4T1 model of mammary tumor progression (Fig. 1B) (26,27). Indeed, the highly metastatic 4T1 and 66c14 cells expressed significantly more p130Cas than did their moderately metastatic counterparts, 168-Farn and 4T07 (Fig.…”
Section: Elevated P130cas Expression Inhibits Tgf-␤-mediatedmentioning
confidence: 48%
“…Along these lines, we also observed p130Cas expression to be up-regulated dramatically in the murine 4T1 model of mammary tumor progression (Fig. 1B) (26,27). Indeed, the highly metastatic 4T1 and 66c14 cells expressed significantly more p130Cas than did their moderately metastatic counterparts, 168-Farn and 4T07 (Fig.…”
Section: Elevated P130cas Expression Inhibits Tgf-␤-mediatedmentioning
confidence: 48%
“…31,32 Importantly, both TrkC and ETV6-NTRK3 have been reported to bind to and inhibit TGFβRII, thereby negatively regulating SMAD phosphorylation and downstream TGFβ signaling. 35,36 To investigate whether TSPYL2 is required for RESTmediated TrkC repression, we first overexpressed TSPYL2 in A549 cells and found that TSPYL2 decreased TrkC mRNA and protein levels (Figures 4a and b). Interestingly, we also noticed that TrkC was induced by TGFβ in A549 cells, but that TSPYL2 completely abrogated this increase (Figure 4a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Bambi, a T␤RI-related protein lacking a cytoplasmic kinase domain, acts as a pseudoreceptor by binding endogenous T␤RI and T␤RII, preventing receptor activation (65,66). TrkC, a member of the Trk family of neurotrophin receptors and Etv6-Ntrk3, a chimeric tyrosine kinase, bind to T␤RII and suppress T␤RII from activating T␤RI (67,68). A cholesterol-rich membrane microdomain marker caveolin-1 associates with T␤RI, leading to the internalization of T␤RI into caveolin-1 positive vesicles and its subsequent degradation via the proteasome pathway (69,70).…”
Section: Discussionmentioning
confidence: 99%